Crowd Evacuation Behaviour Modeling and Simulation in 3D Platform - Hamizan, Binti Sharbini; Azlina, Binti Ahmadi Julaihi; Tan, Ping Ping; Chiu, Po Chan (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
Crowd simulation is an active research domain and is crucial for simulating crowd behaviour in certain condition such as normal or panic situation. The simulation is to show the interaction between the individual in a crowd. Nowadays, there are many kinds of scenarios as well as simulation softwares that can be adapted to simulate a crowd simulation such as during emergency situation e.g. building evacuation. Crowd simulation in three-dimensional platform is fairly important in order to have a more realistic looks and movement of the crowd in one particular environment. The evacuation simulation is useful for the crowd in one confinement to seek for a safe exit path in shortest time possible and thus increase the occupant’s safety. The evacuation time is said to be in safe condition if all the evacuees successfully can get through the exit in minimal time. To aid in minimal exit time, the concept of faster-is-slower (bottleneck) must be solved as it can lead to more waiting time or delay during evacuation process. In this paper, it will discuss about the crowd simulation behavior, crowd simulation based on agent-based model, existing crowd simulation tools and the result of simulating the three-dimensional (3D) crowd evacuation time based on a number of exits variation in panic situation. The tools used to carry out the experiment is Anylogic software whereby the results show that it adheres to shorter evacuation time when the number of exit increases. The 3D layout design was following the original layout the faculty’s lower ground floor where the classrooms are mostly resided. The simulation is useful in order to estimate of evacuation time with different total number of exits to alleviate the faster-is-slower effect in case of any emergency situation happens at the faculty building